Pengaruh Pemberian Sari Kacang Hijau (Vigna radiata (L.) R. Wilczek) Terhadap Densitas Tulang dan Jumlah Osteoklas pada Tikus(Rattus norvegicus) yang Diovariektomi - Yeyen, Arnita; Bahtiar, Anton; Soetanto, Sriangky (Jurnal Farmasi Indonesia, 2016)
Greenbean (Vigna radiata (L.) R. Wilczek) contained phytoestrogen suspected has a potential effect as an preventive and alternative treatment of osteoporosis. This study is proposed to determine the effect of extracts of greenbean juice (Vigna radiata (L.) R. Wilczek) on bone density by measuring calcium levels using Atomic Absorption Spectrofotometry (AAS) from femur and the number of osteoclasts collected from histological object which made from ovariectomized rat tibia. Ovariectomy method conducted to represent the osteoporosis condition on 36 female Sprague Dawley rats were divided into 7 groups. Group 1 noticed as Sham was the rat control with surgery without ovariectomy and distilled water, group 2 as negative control is given distilled water and ovariectomized rat control, group 3 as positive control was given estradiol and ovariectomized rat control, group 4 as positive control was given vitamin E and ovariectomized rat control. Group 5, 6, and 7 were given 50 g/100 ml the greenbean juice with volume variation 5 ml/200 gBW, 2.5 ml/200 gBW, and 1.25 ml /200 gBW. Six groups had ovariectomized except sham group and rested for 20 days. Greenbean juice was given orally once daily started from day 21 until day 50. Calcium concentration and osteoclast measurement process taken on day 51. The results of bone calcium levels and osteoclast number showed that greenbean juice did not give significant differences among ovariectomized rats.